Microbial Characteristics and Functions in Coffee Fermentation: A Review - Xiaojing Shen; Qi Wang; Hongsheng Wang; Guoqing Fang; Ying Li; Jilai Zhang; Kunyi Liu (Fermentation)
Based on coffee’s unique and fascinating flavor, coffee has become the most popular nonalcoholic drink in the world and is a significant agricultural economic crop in tropical- and subtropical-planted coffee countries and regions. It is also beneficial for human health because of its rich active compounds, such as caffeine, chlorogenic acids, trigonelline, tryptophan alkaloids, diterpenes, melanoidins, etc. These compounds often relate to the prevention of cardiovascular disease, Alzheimer’s disease, and antibacterial, anti-diabetic, neuroprotection, and anti-cancer activities. The formation of coffee’s flavor results from various influence factors, including genetics, shade, elevation, post-harvest processing, fermentation, roasted methods, etc. The first stage of coffee production is obtaining green coffee beans through the primary process. Fermentation is critical in the primary process of coffee, which is often related to yeasts, bacteria, and filamentous fungi. Therefore, microorganisms play a key role in coffee fermentation and coffee flavor. To provide an understanding of the role of microorganisms in coffee fermentation, the coffee fermentation overview and microbial characteristics in different coffee primary processing methods and different coffee fermentation regions were reviewed in this paper. Brazil and China are the main study countries in coffee fermentation, which contribute a large number of technologies and methods to improve coffee flavor by fermentation. Different primary processing methods (wet, dry, or semi-dry processing) and coffee producer countries had obvious microbial community characteristics. Moreover, the application of yeast and bacteria for improving coffee flavor by microbial fermentation was also introduced.